2009
DOI: 10.1094/ats-2009-0720-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Tolerance on ‘Sea Spray’ Seashore Paspalum Seedlings

Abstract: There are no reports of herbicide tolerance on seedling seashore paspalum (Paspalum vaginatum Sw.). The objective of this study was to determine which herbicides cause the least amount of injury to seashore paspalum seedlings and allow for maximum establishment. Field studies were conducted in 2007 and 2008 to assess the tolerance of ‘Sea Spray’ seashore paspalum to 23 herbicides. Herbicide treatments were applied two weeks after emergence of seedlings and compared to an untreated control. MSMA, imazaquin, flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…McCullough et al (2012b) found applications of sulfentrazone at 0.42 kg ai ha À1 caused , 20% injury to actively growing Sea Isle I seashore paspalum at 1 and 3 WAT. In other experiments, carfentrazone treatments caused , 15% injury to seashore paspalum seedlings (Patton et al 2009). Applications of flumioxazin may cause unacceptable injury to actively growing seashore paspalum, but treatments may be safely applied at , 10% green cover.…”
Section: Resultsmentioning
confidence: 85%
“…McCullough et al (2012b) found applications of sulfentrazone at 0.42 kg ai ha À1 caused , 20% injury to actively growing Sea Isle I seashore paspalum at 1 and 3 WAT. In other experiments, carfentrazone treatments caused , 15% injury to seashore paspalum seedlings (Patton et al 2009). Applications of flumioxazin may cause unacceptable injury to actively growing seashore paspalum, but treatments may be safely applied at , 10% green cover.…”
Section: Resultsmentioning
confidence: 85%
“…For example, foramsulfuron, rimsulfuron, and trifloxysulfuron are effective POST herbicides for annual bluegrass control in bermudagrass ( Cynodon dactylon L.) and zoysiagrass ( Zoysia spp. ), but may cause excessive injury (>20%) to seashore paspalum (12, 21, 22, 25). Ethofumesate has potential for use in seashore paspalum, but applications are often injurious and are limited to early POST timings for annual bluegrass control (4, 11, 12, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Preemergence (PRE) herbicides, including dinitroanilines and oxadiazon, may be applied in fall for annual bluegrass control in seashore paspalum (21). However, POST annual bluegrass control is difficult due to a lack of selective graminicides safe on seashore paspalum.…”
mentioning
confidence: 99%
“…Sulfonylureas such as foramsulfuron, rimsulfuron, and trifloxysulfuron are effective POST herbicides for annual bluegrass control in warm-season grasses but may cause excessive injury (. 20%) to seashore paspalum (Johnson and Duncan 2000;Patton et al 2009;Toler et al 2007;Unruh et al 2006). Ethofumesate has potential for use in seashore paspalum but applications are limited to early POST timings for annual bluegrass control as efficacy is often reduced on mature plants in spring (Coats and Krans 1986;Johnson 1983).…”
mentioning
confidence: 99%